2007
DOI: 10.7326/0003-4819-147-5-200709040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Serologic Tests and HLA-DQ Typing for Diagnosing Celiac Disease

Abstract: In a patient population referred for symptoms and signs of celiac disease with a prevalence of celiac disease of 3.46%, TGA and EMA testing were the most sensitive serum antibody tests and a negative HLA-DQ type excluded the diagnosis. However, the addition of HLA-DQ typing to TGA and EMA testing, and the addition of serologic testing to HLA-DQ typing, provided the same measures of test performance as either testing strategy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(148 citation statements)
references
References 36 publications
4
135
0
9
Order By: Relevance
“…The production of EMA and ⁄ or tTGA is known to be essentially restricted to HLA-DQ2 and ⁄ or -DQ8 positive persons. 19,20 Although the existence of fluctuating coeliac antibody levels in children who are genetically predisposed for CD has previously been described, the underlying pathophysiological mechanism is not well understood yet. 12,[21][22][23][24] Previous research has suggested different explanations for fluctuating antibody levels, including environmental factors such as the increase in gluten intake and ⁄ or gastro-intestinal infections, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The production of EMA and ⁄ or tTGA is known to be essentially restricted to HLA-DQ2 and ⁄ or -DQ8 positive persons. 19,20 Although the existence of fluctuating coeliac antibody levels in children who are genetically predisposed for CD has previously been described, the underlying pathophysiological mechanism is not well understood yet. 12,[21][22][23][24] Previous research has suggested different explanations for fluctuating antibody levels, including environmental factors such as the increase in gluten intake and ⁄ or gastro-intestinal infections, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A positive anti-tTG was found in 3.1%, and the prevalenc e of CD in the serologic ally sc reened sample was 2.3%. When a similar study was performed in a university hospital, the prevalenc e of CD was 3.5%, and a negative HLA-DQ type exc luded the diagnosis [52] . However, the "addition of HLA-DQ typing to TGA and EMA testing, and the addition of serologic al testing to HLA-DQ typing, provided the same measures of test performanc e as either testing strategy alone" [52] .…”
Section: Serologymentioning
confidence: 99%
“…ese aberrant T-cells are thought to be the origin of enteropathy associated T-cell lymphomas (EATL), and RCD type II patients have thus an increased risk to develop an EATL. While antibodies against tissue transglutaminase (TG2A) are highly sensitive and speci c for the diagnosis of active CD [3], currently there are no biochemical parameters that can aid in the diagnosis of RCD; diagnosis relies on invasive endoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%